To Study the Seismic Analysis of An Existing RC Structure By Using STAAD Pro - Siddhanth Sen (AG Volumes, 2021)
India is one of the most earthquake inclined nations on the planet and has encountered a few significant or moderate earthquakes during the most recent 15 years. Around 50-60 % of the absolute zone of the nation is defenseless against seismic movement of shifting forces. A live project of G+2 existing old structure, structure is modeled and analyzed in STAAD. Pro with existing strength determine from NDT and then providing extra columns, thickness and struts at places where strength is at failure. Comparative analysis is done in between the existing structure and the proposed structure which can easily overcome the failures seen by existing structure proven in the results of NDT.